Determinan Komitmen Organisasi dan Partisipasi Anggaran Terhadap Penerapan Green Economy Studi Pada Perusahaan Property - Arlis D. Kuraesin; Asyari; Maria Suryaningsih (CV ODIS, 2022)
This study aims to examine the influence of organizational commitment and participation of the budget in Green economy implementation. The continued development of the business industry makes green property companies must have a specific strategy to increase competitiveness and provide long-term capacity in the face of competition. Industry implements the concept of green property that support a healthy business climate, efficiency and transparency, implementation of laws and regulations, and consistent law enforcement. The method used in the research is the survey method with sampling using the technique of Systematic Random Sampling With homeowner respondents on housing Ciputra Indah Bekasi. The results showed that organizational commitment significantly influences the implementation of a green economy. And participation budget also has a significant effect on the implementation of a green economy